Efficacy of Baduanjin for obesity and overweight: a systematic review and meta-analysis - Gao, Hainan; Li, Xue; Wei, Hongnan; Shao, Xinxin; Tan, Zili; Lv, Shaowei; Pan, Lijie; Yu, Ting; Ye, Qiuyan; Zhang, Haibo; Zhu, Xiangyu (Frontiers in Endocrinology, 2024)
Background: According to data from the World Health Organization (WHO), there is a significant public health issue regarding the escalating number of individuals affected by obesity and overweight on an annual basis. Therefore, it is imperative to urgently identify interventions that can effectively control and improve this condition. Baduanjin, as a medium intensity exercise, presents itself as a suitable approach for weight reduction among obese individuals. This paper aims to provide a systematic review and meta-analysis of the efficacy of Baduanjin in addressing obesity and Overweight, with the ultimate goal of assisting obese individuals in finding an effective, safe, and engaging method for weight reduction.Methods:We conducted a comprehensive search of multiple databases including PubMed, Cochrane Library, Web of Science, Embase, The China National Knowledge Infrastructure (CNKI), The Chinese Scientific Journal Database (VIP), The Chinese Biomedical Literature Database (CBM), and WanFang database to identify relevant articles published from the inception of each database until September 2023. Specifically, we focused on randomized controlled trials (RCTs) investigating the effects of Baduanjin on weight reduction. Data pertaining to these studies were extracted and analyzed using appropriate statistical methods. In cases where there was no significant heterogeneity (I 2 <50% and P>0.1), we employed a fixed-effects model for data synthesis; Otherwise, the random effects model will be selected. Funnel plots were employed to assess publication bias, and mean difference (MD) was reported as an indicator of treatment group differences.Results: A total of 420 participants were included in the 10 studies. The body weight(BW) outcomes of the experimental group compared with the control group was ([MD= -3.69, 95% CI= (-4.97, -2.40)], (P < 0.001), body mass index(BMI) ([MD= -5.42, 95% CI= (-6.56, -4. 28)], P < 0.001), waist circumference(WC) ([MD= -1.36,95% CI= (-1.76, -0.96)], P<0.001), hip circumference(HC) ([MD= -3.40, 95% CI= (-4.43, -2.37)], P < 0.001), waist-hip ratio (WHR) ([MD= -0.03, 95% CI= (-0.04, -0.02)], P > 0.1). All of them in the experimental group had significant difference. Egger 's test(t=1.43,P=0.190 ) suggested there was no substantial bias present within the data analysis process.The safety profile revealed no adverse events reported across all ten studies.